2012
DOI: 10.1016/j.drugalcdep.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of alcohol dependence: Advancing towards systems-based approaches

Abstract: BACKGROUND Personalized treatment for psychopathologies, in particular alcoholism, is highly dependent upon our ability to identify patterns of genetic and environmental effects that influence a person’s risk. Unfortunately, array-based whole genome investigations into heritable factors that explain why one person becomes dependent upon alcohol and another does not, have indicated that alcohol’s genetic architecture is highly complex. That said, uncovering and interpreting the missing heritability in alcohol g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 162 publications
0
19
0
Order By: Relevance
“…Perhaps, innovative system-based approaches as recently described (Palmer et al, 2012) will identify mechanisms that may provide new targets for the treatment of AUDs.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, innovative system-based approaches as recently described (Palmer et al, 2012) will identify mechanisms that may provide new targets for the treatment of AUDs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the 293 iMO–human genes were queried against a set of 732 human genes compiled from (i) several comprehensive reviews on the genetics of AUD (Edenberg and Foroud, 2013, 2014; Palmer et al, 2012; Rietschel and Treutlein, 2013; Schuckit, 2014) and (ii) genes in the HuGe Navigator (Yu et al, 2008) identified by the search terms “alcoholism.” A small number of these 732 human genes have established roles in AUD, whereas the remaining genes have been implicated in AUD by smaller scale studies, single studies only, etc. Although very few of the 732 genes were implicated by studies that observed formal statistical significance of association with AUD, we included all 732 genes in our analyses in an attempt to capture the broad landscape of genetic findings from studies in humans.…”
Section: Genetics Of Alcohol Behavior In Invertebrate Model Organism mentioning
confidence: 99%
“…In such a case, the iMO data would provide strong evidence for a role of the biochemical process in alcohol-related behavior relevant to human AUD, even in the absence of directly implicating the particular orthologous human gene. Thus, as a complement to our analysis of the overlap between individual iMO and human genes, we visually compared the predicted or known biochemical functions of the iMO genes (Tables 1 and 2) with the functions of genes described in several comprehensive reviews on the genetics of AUD (Edenberg and Foroud, 2013, 2014; Palmer et al, 2012; Rietschel and Treutlein, 2013; Schuckit, 2014). As is true for individual genes, the most compelling evidence for a pathway important in iMOs and humans is for the alcohol-metabolizing machinery of ADH and ALDH.…”
Section: Genetics Of Alcohol Behavior In Invertebrate Model Organism mentioning
confidence: 99%
“…subtypes of alcohol dependence with higher vs. lower heritability) and (b) advanced analytic techniques that make use of both array and next-generation sequencing technologies [193]. A comprehensive discussion of studies applying these approaches is beyond the scope of this review, but we refer to recent review papers that cover GWAS of alcohol dependence [182,186,194,195,196]. A potential future challenge might be posed by the change in diagnostic criteria with the publication of DSM-V [6].…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%